Sustainability of Rooftop Gardening Adoption in Urban Residential Areas from Future Homebuyers’ Perspective in Malaysia - Amran, Syakir Haziq; Salahudin, Shahrul Nizam (Research in Management of Technology and Business, 2023)
Malaysia’s agriculture sector has been gradually declining over decades due to the increasing food imports and lack of land for agricultural activities. This study aims to identify the issues, drivers, and future trends of rooftop gardening adoption in urban residential areas from future homebuyers’ perspective in Malaysia, which will be derived from the target respondents based in the Kuala Lumpur, since Kuala Lumpur has become a focal point in Malaysia. Descriptive questionnaire developed based on social, technological, economic, environmental, political, and values (STEEPV) drivers will be used to collect the data from respondents. In this study, four types of data analysis will be used which are STEEPV analysis, descriptive analysis, impact-uncertainty analysis, and scenario building, and the data will be analysed using the Statistical Package for Social Science (SPSS) version 26. The analysed data will identify the sustainability and future trends of implementing rooftop gardening in urban residential areas. This research signifies whether the rooftop gardening adoption is gaining acceptance among future homebuyers.